Speed of life - Weston, Carol (Sourcebooks Jabberwocky, 2017)
Missing her mother who died last year, fourteen-year-old Sofia finds an anonymous outlet for her personal questions and deep, dark secrets in the Dear Kate advice columnist, until, much to her horror, Sofia's father starts dating Kate.